Tocilizumab and Renal Artery Stent–Therapeutic Strategy for Takayasu Arteritis - Srividhya Karunanithi; Subramanian Nallasivan; Mariappan Murugan (Journal of Clinical Rheumatology and Immunology, 2022)
Takayasu vasculitis (TAK) is a form of large vessel vasculitis clinically manifesting as pulseless disease or hypertension. It is more common in South East Asia and Japan, India, and Mexico [1]. It is increasingly being recognized due to increased awareness among medical fraternity and better imaging modalities. Undetected hypertension, pulselessness, and syncope are more common symptoms and presentation during pregnancy is unusual and can lead to bad obstetric outcomes. Recent evidences support the use of tocilizumab for inducing remission in Takayasu arteritis. We report this rare case of vasculitis presenting in pregnancy as malignant hypertension. A 20-year-old pregnant woman (45 days) presented with headache and nausea but no fever. She had a history of intermittent claudication of legs for the past 3 years but not evaluated. During examination, pulses were felt normally and blood pressure (BP) 180/110, no murmurs in cardiac auscultation, but she had abdominal bruit (renal vessels). Other systems were normal. Echocardiogram (ECHO) showed dilated ascending aorta. Doppler of renal vessels showed narrowing of renal arteries. Unfortunately, she had to undergo termination of pregnancy (high BP in spite of antihypertensives). Her computed tomography (CT) angiogram showed features of TAK with type 5 pattern–she had methylprednisolone infusion 500 mg daily for 3 days, followed by injection tocilizumab 400 mg monthly 3 doses. Once remission was achieved, she had recanalization by percutaneous transluminal angioplasty of right renal artery. She is currently maintained on aspirin and telmisartan. Awareness of causes of high BP, inputs by radiologist, cardiologist, and rheumatologist and understanding by the patient and family helped to achieve good outcome albeit the miscarriage.